معوقات استخدام عقد المضاربة كنظام تمويل إسلامي - حجاري, محمد (جامعة الوادي University of Eloued, 2019)
يمثل عقد المضاربة النموذج الحقيقي لدور المصارف الإسلامية التنموي، نظرا لاستبداله خدمة المديونية بمعدلات الربح المشترك بين المصرف والمضارب، عن طريق عقود استثمار تقوم على مبدأ التشغيل الكامل لعناصر الإنتاج، بعيدا عن الفائدة الربوية التي تنتج عن القروض العادية، إضافة إلى أنه متاح في المشاريع المتوسطة والصغيرة بخلاف صور أخرى للتمويل البنكي. ومع ذلك؛ تعترض هذا النوع من العقود معوقات بعضها هيكلية ومؤسساتية، وبعضها الآخر فنية، إلا أن العائق الأبرز يتمثل في المعوقات القانونية، التي تتلخص في الأدوات القانونية المتعلقة بالقانون الجبائي، وقانون النقد والقرض، والتي لا تتفق مع الصيرفة الاسلامية. وهذا ما جعل كثيرا من المصارف تلجأ لعقود المرابحة، وعلى الرغم من سهولته إلا أنه تعتريه مخالفات شرعية عديدة. The Mudaraba contract represents the real model for the role of Islamic Development Banks, considering that it replaces the debt service with the common profit rates between the bank and the Mudarib through investment contracts based on the principle of full operation of the elements of production, away from the interest rate generated by ordinary loans, and is available in medium and small enterprises unlike other forms of bank financing. However, these types of contracts are embarassed by structural, institutional and other technical constraints, while the main obstacle is legal considering legal instruments in fiscal law, monetary and credit law , which is not in accordance with Islamic banking. Hence, this has made many banks resort to Murabaha contracts, and despite it’s easiness, it involves many legal irregularities.
تقييم للمعوقات وتأثيرها في التنمية الاقتصادية
Keywords: عقد المضاربة، صيرفة إسلامية، استثمار، معوقات، تنظيمية، قانونية; Mudaraba contract, Islamic banking, investment, obstacles, regulatory, legal.